Chinese Investment in Ghana's Manufacturing Sector - Tang Xiaoyang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
This paper uses Ghana as a case study to illustrate the extent to which Chinese manufacturing firms are driving manufacturing in an African country. Through the combination of desktop and field research, the author finds that the total number of Chinese manufacturing investments in Ghana indeed has been increasing during past decades, but quite a few projects were abandoned or not implemented due to concern over the unfavorable investment environment. The weak economic environment of Ghana itself proved to be limiting the technology transfer and local linkage between Chinese firms and Ghanaians.
Keywords: 330